Q. 1 D5.0( 6 Votes )

<span lang="EN-US

Answer :

(x - 3)(2x + 1) = x(x + 5)

Here LHS = (x - 3)(2x + 1) = 2x2 - 6x + x - 3 = 2x2 - 5x - 3


RHS = x(x + 5) = x2 + 5x


Equating LHS and RHS


2x2 - 5x - 3 = x2 + 5x


x2 - 10x - 3 = 0 which is of the form ax2 + bx + c = 0


it is a quadratic equation.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Introduction to Linear Equations in Two VariablesIntroduction to Linear Equations in Two VariablesIntroduction to Linear Equations in Two Variables62 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

<span lang="EN-USAP- Mathematics

Represent tAP- Mathematics

<span lang="EN-USAP- Mathematics